Bridging the Gap: Using Wild African Elephant Metabolic, Reproductive, and Stress Hormone Profiles to Enhance Management in Human Care - Kaitlyn M. Campbell; Chelsi J. Marolf; Peter E. Buss; Kari A. Morfeld (Animals, 2025)
Understanding hormone patterns in free-ranging African elephants can provide critical insights for the management of elephants in human care, particularly in addressing reproductive anomalies and the rising prevalence of obesity in zoo populations. This study is the first to establish baseline values for glucose, insulin, and leptin, and their potential relationships with reproductive and stress hormones. We measured the hormones in serum samples collected opportunistically in Kruger National Park between 2000 and 2016. Endocrine profiles were compared across age groups in both male and female elephants and between the wet and dry seasons. In females, progestogen and prolactin levels were highest in adults, and were not significantly correlated with the glucose-to-insulin (G/I) ratio or leptin. In males, testosterone levels were higher in adults, and the G/I ratio was a significant predictor of testosterone concentrations. Seasonal variations revealed that, in males, testosterone levels were higher, and cortisol concentrations were lower during the rainy season. In females, cortisol concentrations were negatively associated with progestogen levels during the dry season. These benchmarks offer zoos a reference point to assess whether current management approaches are effective, and how natural variation with the season may impact hormone levels.